APPROXIMATION OF FUNCTIONS FROM THE CLASSES Cψ β,∞ BY BIHARMONIC POISSON INTEGRALS - Kharkevych, Yurii I.; Zhyhallo, Kostiantyn M.; Харкевич, Юрій Іліодорович; Жигалло, Костянтин Миколайович (Ukrainian Mathematical Journal, 2011)
We deduce asymptotic equalities for the upper bounds of deviations of biharmonic Poisson integrals on the classes of ( ψ, β )-differentiable periodic functions in the uniform metric.